2016
DOI: 10.1159/000445106
|View full text |Cite
|
Sign up to set email alerts
|

Skin Wound Repair Is Not Altered in the Absence of Endogenous AnxA1 or AnxA5, but Pharmacological Concentrations of AnxA4 and AnxA5 Inhibit Wound Hemostasis

Abstract: Skin injury induces the cell surface exposure of phosphatidylserine (PS) on damaged and dying cells to activate coagulation and repair processes. Annexins can bind to PS and may modulate the healing response. Here, we determine the relevance of annexins for skin wound healing using AnxA1- and AnxA5-deficient mice and recombinant annexins with distinct PS binding properties. Wound inflammation, closure and the formation of granulation tissue were not altered in AnxA1- or AnxA5-deficient mice or after increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…At early time points of the healing process, the wound is mainly repopulated by hematopoietic cells [32]. At day three and five post wounding the majority of the cells are macrophages whereas fibroblasts, vascular cells, neutrophils or platelets are hardly found within the wound bed [14,32,33]. We confirmed by immunofluorescence studies that at day three post wounding F4/80 + macrophages are found within the wound bed (Figure 5a).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…At early time points of the healing process, the wound is mainly repopulated by hematopoietic cells [32]. At day three and five post wounding the majority of the cells are macrophages whereas fibroblasts, vascular cells, neutrophils or platelets are hardly found within the wound bed [14,32,33]. We confirmed by immunofluorescence studies that at day three post wounding F4/80 + macrophages are found within the wound bed (Figure 5a).…”
Section: Resultssupporting
confidence: 61%
“…To demonstrate that ECM components could be important for macrophage-modulated wound healing, immunofluorescence and immunoblot analysis of mouse skin wounds at the peak of macrophage infiltration were performed. At early time points of the healing process, the wound is mainly repopulated by hematopoietic cells [32]. At day three and five post wounding the majority of the cells are macrophages whereas fibroblasts, vascular cells, neutrophils or platelets are hardly found within the wound bed [14,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy to mention that angiogenesis induced by VEGF-A treatment was similar in wild type (WT) and AnxA1 null mice ( Supplementary Figure 2 ), showing that endogenous AnxA1 is not relevant to the VEGF-A induced angiogenesis in the skin. As previously mentioned, it was recently showed the normal skin repair in AnxA1 null mice ( Kreft et al, 2016 ).…”
Section: Resultsmentioning
confidence: 77%
“…However, the role of AnxA1 on skin repair is not well established. Secreted AnxA1 is not essential to skin wound healing, as wound inflammation, closure and the formation of granulation tissue were not altered in AnxA1 null mice ( Kreft et al, 2016 ). Conversely, we recently showed, for the first time, that the systemic pharmacological treatment using AnxA1 2–26 in mice increased skin allograft survival by inducing the resolution of inflammation, as it caused impaired migration of neutrophils into tissue and enhanced apoptosis of these cells in the site of allograft transplantation ( Teixeira et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One well-known physiological role of several ANXs is the regulation of blood coagulability during coagulation (including thrombosis) and fibrinolysis. [24][25][26] ANXA5 is the most studied ANX in terms of its anticoagulant activity and inhibits coagulation by binding to negatively charged phospholipid membranes, such as those containing phosphatidylserine, and preventing vitamin K-dependent proteins from forming protease complexes on the membrane. [27][28][29] Moreover, an ANXA5 knock-out mouse study showed an increase in placental thrombosis and subsequent fetal loss.…”
mentioning
confidence: 99%